Pengaruh Manajemen Laba, Kinerja Keuangan Perusahaan, Dan Struktur Kepemilikan Saham Terhadap Pengungkapan Corporate Social Responsibility (CSR) - Imelda Wijaya; Kathryn Sugara (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
The purpose of this research is to find out the effect of profit management, company financial performance, and shareownership structure on the disclosure of Corporate Social Resposibility (CSR) in mining companies listed in Indonesia StockExchange for the period 2018-2020. This type of research uses a type of quantitative research. Sampling of this research usingpurposive sampling method. The type of data used is secondary data, with a sample of 108 out of a population of 36 mining companieslisted on the Indonesia Stock Exchange. Analysis techniques used with multiple linear regression analysis. The results showed thatprofit management and company financial performance has no effect on CSR disclosure, while share ownership structure hassignificant effect on CSR disclosure.